Analysis of Multivariate Data Variance Detected Outlier to Determine Factors Influencing Lipid Profile in Diabetes Patients - Rahmah Humaeroh; Muhammad Nur Aidi; Bagus Sartono; Nazarina (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Diabetes is characterized by high blood glucose levels and can lead to cardiovascular complications. This research, will be investigating he factors influencing lipid profile in diabetes patients and the differences in these profiles under various treatments. The research used the MANOVA test to analyze differences in lipid profile under different treatment and controlled for covariates using Mancova. They also used robust methods to address outliers is minimum covariance determinant. The result suggest that gender is a significant factor influencing lipid profile in diabetes patients. The most effective analytical methods were found to be robust manova and robust mancova, with low RMSE values indicating their accuracy.